On the Conformational Dynamics of β-Amyloid Forming Peptides: A Computational Perspective - Saravanan, Konda Mani; Zhang, Haiping; Zhang, Huiling; Xi, Wenhui; Wei, Yanjie (Frontiers in Bioengineering and Biotechnology, 2020)
Understanding the conformational dynamics of proteins and peptides involved in important functions is still a difficult task in computational structural biology. Since such conformational transitions in β-amyloid (Aβ) forming peptides plays crucial role in many neural disorders, researchers from different fields come together to address the folding of Aβ forming peptides. Many theoretical researches have been progressed in recent years on studying Aβ peptides by using mathematical, physico-chemical, molecular dynamics simulations and machine learning approaches. In this article, we comprehensively review about the advances in the development of theoretical models to study Aβ peptide folding and interactions in particular about neural disorders. Further, we extensively review the advances in molecular dynamics simulations as a tool for studying conversion between polymorphic amyloids and applications of using machine learning approaches in predicting Aβ peptides and aggregation prone regions in proteins. Through this paper, we provide a comprehensive view on theoretical advances in study of Aβ peptides which enhances our understanding at molecular level and can ultimately lead to future developments in targeting certain acute neural disorders like Alzheimer’s disease.